Evaluation of GDH and HDP as novel serological biomarkers for Plasmodium falciparum malaria diagnosis across varying parasitemia and transmission settings in India - Amreen Ahmad; Shrikant Nema; Kushagri Arora; Ruhi Sikka; Akansha Singh; Sri Krishna; Mrigendra Pal Singh; Anil Kumar Verma; Nitika Nitika; Anup R. Anvikar; Himanshu Gupta; Praveen Kumar Bharti (PLoS ONE, 2025)
Malaria diagnosis has progressed significantly with the introduction of Rapid Diagnostic Tests (RDTs) targeting Histidine-Rich Protein 2 (HRP2), Lactate dehydrogenase (LDH), and aldolase. However, challenges remain, such as the presence of Plasmodium falciparum histidine-rich protein 2 (pfhrp2) gene deletions and reduced sensitivity in regions with low parasitemia. This study evaluates antibody responses to novel biomarkers—glutamate dehydrogenase (GDH) and Heam detoxification protein (HDP)—in comparison to conventional antigens (HRP2, LDH, and aldolase) across different infection, transmission settings, and parasitemia conditions. We analyzed plasma samples from 928 participants, including 886 P. falciparum-positive cases, using enzyme-linked immunosorbent assay. Our results revealed antibody levels against all studied peptides clear differentiation between malaria-positive and negative samples, with Receiver Operating Characteristic (ROC) curve analysis showing high diagnostic accuracy (Area under the ROC curve > 96%) for detecting P. falciparum infection. However, the sensitivity and specificity for differentiating between endemicity or parasitemia groups were limited for certain peptides. Specifically, GDH2 and HRP2 effectively distinguished parasitemia levels, while GDH2, HDP2, and LDH showed promise in distinguishing between varying endemicity levels. These findings suggest that GDH and HDP have significant potential as reliable serological biomarkers for malaria detection. However, further studies are needed to refine their application in categorizing endemicity and parasitemia. This research highlights the need for adaptable diagnostic tools to address the complex challenges of malaria in endemic regions.